A Monthly Index for the Large‐Scale Sea Surface Temperature Gradient Across the Separated Gulf Stream. Issue 24 (14th December 2022) - Parfitt, R.; Kwon, Y.; Andres, M.
Abstract: The strong sea‐surface temperature (SST) gradient associated with the Gulf Stream (GS) is widely acknowledged to play an important role in shaping mid‐latitude weather and climate. Despite this, an index for the GS SST gradient has not yet been standardized in the literature. This paper introduces a monthly index for the large‐scale SST gradient across the separated GS based on the time‐varying GS position detected from sea‐surface height. Analysis suggests that the variations in the monthly average SST gradient throughout the year result primarily from SST variability to the north of the GS, with little contribution from SST to the south. The index exhibits a weak periodicity at ∼2 years. Sea level pressure and turbulent heat flux patterns suggest that variability in the large‐scale SST gradient is related to atmospheric (rather than oceanic) forcing. Ocean‐to‐atmosphere feedback does not persist throughout the year, but there is some evidence of wintertime feedback. Plain Language Summary: The Gulf Stream is a narrow and fast‐flowing oceanic boundary current that transports warm tropical water north along the coast of Florida and out into the North Atlantic past Cape Hatteras. It is a region where sea‐surface temperatures (SSTs) change dramatically over very short distances with much cooler temperatures on one side of the Gulf Stream (GS) (to the north) and warmer temperatures on the other side (to the south). This strong change in SST across the GS is important for weather systems that propagate in the Euro‐Atlantic sector. Here, an index that measures how much the SSTs change with distance from month‐to‐month across the GS once it separates past Cape Hatteras is developed for the first time. It is found that variability in the index primarily results from SST variations to the north of the separated GS, which themselves are influenced by the atmosphere. There is evidence however that the SST variability represented by the index can also exert an influence on the atmosphere in wintertime. Additionally, the value of the index at any given time seemingly provides some information about the state of the index several years into the future. Key Points: A monthly index for the large‐scale sea‐surface temperature gradient of the separated Gulf Stream is presented Variations in the index throughout the year are related to atmospheric forcing Evidence of ocean‐atmosphere feedback in the index is only apparent in wintertime